Informatics in Schools. Beyond Bits and Bytes: Nurturing Informatics Intelligence in Education 16th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2023, Lausanne, Switzerland, October 23-25, 2023, Proceedings - Pellet, Jean-Philippe; Parriaux, Gabriel (Lecture Notes in Computer Science,, 2023)
This book constitutes the proceedings of the 16th International Conference on Informatics in Schools: Situation, Evolution and Perspectives, ISSEP 2023, held in Lausanne, Switzerland, during October 23-25, 2023. The 14 full papers presented in this book were carefully reviewed and selected from 47 submissions. They are organized in four topical sections named: artificial intelligence and its applications; competitions, problem solving, and computational; robotics and unplugged modalities; and curricula and computer science concepts. This is an open access book.